FRI0020 Next-Generation Sequencing Demonstrates Dynamic Recirculation of B Cell Clones in Ectopic Lymphoid Structures of Sjögren's Syndrome. (9th June 2015) - Murray-Brown, W.; Carlotti, E.; Floyd, J.; Sutcliffe, N.; Tappuni, A.; Vartoukian, S.; Fortune, F.; Mehr, R.; Pitzalis, C.; Bombardieri, M.
Abstract : Background: Sjögren's syndrome (SS) is characterised by immune cell infiltration in the salivary glands (SG) leading to xerostomia (dry mouth) and exocrine dysfunction 1 . B cells play a central role in SS pathogenesis whereby autoreactive B-cells populate ectopic germinal centres (EGC) in SS-SG and undergo somatic hypermutation and class-switch recombination of the immunoglobulin (Ig) genes 2 . However, the capacity of specific B cell clones to seed ECG in different SG and undergo clonal diversification is unclear. Objectives: To unravel the dynamics of recirculation of B cell clones among different minor salivary gland (mSG) biopsies, we investigated immunoglobulin heavy chain (IgH) gene rearrangements and patterns of somatic hypermutation (SHM) using a high-throughput next-generation sequencing approach. Methods: IgH gene usage and SHM were investigated in 4 pairs of mSG biopsies from 4 pSS patients with high B cell infiltration and EGC. Retro-transcription of 100ng total RNA using Ig-μ, -γ and -α specific primers yielded Ig-specific cDNA for use as template in producing 36 PCR libraries (12 forward primers for each Ig-C) per sample 3 . Modified primers 3 allow for multiplexing of amplicons and assist in bioinformatic filtering of reads. Sequencing was performed using the Roche GS-FLX titanium platform that allows for bi-directional sequencing producing full length reads of ∼500bp. Raw data was processed using IGMT 4 and IgAT 5, and lineage trees were produced using IgTree © 6 . Results: We generated ∼166, 000 reads for the 8 SS mSG samples. Ig isotype usage was similar between paired samples; patients 1-3 presented with ∼60% μ- and ∼30% α-gene usage; and patient 4 contained a predominance of γ-gene usage (∼60%) and approximately equal usage of μ and α (∼20%). In total, we detected 1631 clonotypes (defined as reads with same IgHV and IgHJ gene usage and equal CDR3 length). Between 5 and 9 shared clonotypes were observed among paired SG biopsies, demonstrating B cells can recirculate between glands. Lineage tree analysis revealed 3 patterns of B cell circulation: a) unidirectional circulation of B cell clones from 1 biopsy to another; b) clones circulating between both glands; c) an undefined pattern with less-mutated and unidentified precursors migrating from one site to the other. Finally, mRNA expression of AICDA, the enzyme required for SHM, correlated with the number of SHMs present in the shared clonotypes studied, supporting the notion that functional EGCs support clonal selection in SS. Conclusions: We show that B cells recirculate between mSG in SS and undergo further rounds of SHM in adjacent glands. The level of B cell recirculation appears to be related to the Ig isotype, as Gamma rich samples appeared to recirculate less often. Although further study is needed to confirm these observations, these findings demonstrate the dynamic nature of B cell affinity maturation in SS within ECGs. References: Voulgarelis & Tzioufas. Nat Rev Rheumatol (2010). Bombardieri, et al. J Immunol (2007). Tiller, Busse & Wardemann. J Immunol Methods (2009). Brochet, Lefranc & Giudicelli. Nucleic Acids Res (2008). Rogosch, et al. Front. Immun (2012). Barak, et al. J Immunol Methods (2008). Disclosure of Interest: None declared